Colorimetric sensing of hydrogen peroxide using capped Morus nigra-sawdust deposited zinc oxide nanoparticles via Trigonella foenum extract - Nishan, Umar; Zahra, Tabassum; Badshah, Amir; Muhammad, Nawshad; Afridi, Saifullah; Shah, Mohibullah; Khan, Naeem; Asad, Muhammad; Ullah, Riaz; Ali, Essam A.; Chen, Ke (Frontiers in Bioengineering and Biotechnology, 2024)
Hydrogen peroxide (H2O2) is one of the main byproducts of most enzymatic reactions, and its detection is very important in disease conditions. Due to its essential role in healthcare, the food industry, and environmental research, accurate H2O2 determination is a prerequisite. In the present work, Morus nigra sawdust deposited zinc oxide (ZnO) nanoparticles (NPs) were synthesized by the use of Trigonella foenum extract via a hydrothermal process. The synthesized platform was characterized by various techniques, including UV-Vis, FTIR, XRD, SEM, EDX, etc. FTIR confirmed the presence of a Zn‒O characteristic peak, and XRD showed the hexagonal phase of ZnO NPs with a 35 nm particle size. The EDX analysis confirmed the presence of Zn and O. SEM images showed that the as-prepared nanoparticles are distributed uniformly on the surface of sawdust. The proposed platform (acetic acid-capped ZnO NPs deposited sawdust) functions as a mimic enzyme for the detection of H2O2 in the presence of 3,3′,5,5′-tetramethylbenzidine (TMB) colorimetrically. To get the best results, many key parameters, such as the amount of sawdust-deposited nanoparticles, TMB concentration, pH, and incubation time were optimized. With a linear range of 0.001–0.360 μM and an R2 value of 0.999, the proposed biosensor’s 0.81 nM limit of quantification (LOQ) and 0.24 nM limit of detection (LOD) were predicted, respectively. The best response for the proposed biosensor was observed at pH 7, room temperature, and 5 min of incubation time. The acetic acid-capped sawdust deposited ZnO NPs biosensor was also used to detect H2O2 in blood serum samples of diabetic patients and suggest a suitable candidate for in vitro diagnostics and commercial purposes.